THE IMPACT OF THE QUIET QUITTING PHENOMENON ON EMPLOYEES IN SERBIA - Jelača, Sanja; Golubović, Marko (The European Journal of Applied Economics, 2024)
Employees play a pivotal role in organizational functionality, underscoring the crucial importance of effective human resources management. In recent years, the global dissemination of a workplace behavior concept termed 'quiet quitting' has gained momentum through online platforms. This behavioral model involves employees performing the minimum required, showing reluctance to exceed expectations. This study explores the prevalence of 'quiet quitting' in organizations within Serbia, utilizing survey methodology. Our findings suggest that, rather than a novel concept, 'quiet quitting' represents a contemporary label for an enduring behavior, characterizing individuals with limited workplace engagement often rooted in job dissatisfaction. While 'quiet quitting' is not widely recognized in Serbia at present, Generation Z members exhibit heightened susceptibility. This research, first of its kind in Serbia, aligns with the identified global phenomenon, establishing a foundation for extensive exploration within both business and academic realms. Our extensive conclusions underscore the need for continued investigation into quiet quitting, contributing valuable insights for organizations seeking to comprehend, address, and elevate the discourse on employee engagement within the Serbian professional landscape.
Keywords: quiet quitting; Serbia; employee engagement; burnout; human resources